The Structure of Human Parechovirus 1 Reveals an Association of the RNA Genome with the Capsid - Kalynych, Sergei; Pálková, Lenka; Plevka, Pavel (Journal of virology, 2016)
UNLABELLED: Parechoviruses are human pathogens that cause diseases ranging from gastrointestinal disorders to encephalitis. Unlike those of most picornaviruses, parechovirus capsids are composed of only three subunits: VP0, VP1, and VP3. Here, we present the structure of a human parechovirus 1 (HPeV-1) virion determined to a resolution of 3.1 Å. We found that interactions among pentamers in the HPeV-1 capsid are mediated by the N termini of VP0s, which correspond to the capsid protein VP4 and the N-terminal part of the capsid protein VP2 of other picornaviruses. In order to facilitate delivery of the virus genome into the cytoplasm, the N termini of VP0s have to be released from contacts between pentamers and exposed at the particle surface, resulting in capsid disruption. A hydrophobic pocket, which can be targeted by capsid-binding antiviral compounds in many other picornaviruses, is not present in HPeV-1. However, we found that interactions between the HPeV-1 single-stranded RNA genome and subunits VP1 and VP3 in the virion impose a partial icosahedral ordering on the genome. The residues involved in RNA binding are conserved among all parechoviruses, suggesting a putative role of the genome in virion stability or assembly. Therefore, putative small molecules that could disrupt HPeV RNA-capsid protein interactions could be developed into antiviral inhibitors. IMPORTANCE: Human parechoviruses (HPeVs) are pathogens that cause diseases ranging from respiratory and gastrointestinal disorders to encephalitis. Recently, there have been outbreaks of HPeV infections in Western Europe and North America. We present the first atomic structure of parechovirus HPeV-1 determined by X-ray crystallography. The structure explains why HPeVs cannot be targeted by antiviral compounds that are effective against other picornaviruses. Furthermore, we found that the interactions of the HPeV-1 genome with the capsid resulted in a partial icosahedral ordering of the genome. The residues involved in RNA binding are conserved among all parechoviruses, suggesting an evolutionarily fixed role of the genome in virion assembly. Therefore, putative small molecules disrupting HPeV RNA-capsid protein interactions could be developed into antiviral inhibitors.
Keywords: krystalografie rentgenová; molekulární modely; RNA virová; Models, Molecular; Crystallography, X-Ray; kapsida; Protein Binding; Parechovirus; vazba proteinů; Capsid; RNA, Viral